Infection risk in patients with autoimmune cytopenias and immune dysregulation treated with mycophenolate mofetil and sirolimus - Comella, Mattia; Palmisani, Elena; Mariani, Marcello; Dell’Orso, Gianluca; Licciardello, Maria; Giarratana, Maria Carla; Arcuri, Luca; Pestarino, Sara; Grossi, Alice; Lanciotti, Marina; Brucci, Giorgia; Guardo, Daniela; et al. (Frontiers in Immunology, 2024)
Introduction: Autoimmune cytopenias are a group of disorders characterized by immune-mediated destruction of blood cells. In children they are often secondary to immune dysregulation which may require long-lasting immunosuppression. Mycophenolate mofetil and sirolimus represent two well tolerated options to treat these disorders, often as a steroid-sparing option. However, no data are available on the infection risk for patients undergoing long-lasting treatments.Patients and Methods: The rate of Severe Infective Events was calculated in episodes per 100/ person/ months at risk (p/m/r) documented by the analysis of hospitalization charts between January 2015 and July 2023 of patients treated with mycophenolate mofetil or sirolimus given for isolated autoimmune cytopenia or autoimmune cytopenias associated with ALPS/ALPS-like syndromes in two large Italian pediatric hematology units.Results: From January 2015 to July 2023, 13 out of 96 patients treated with mycophenolate mofetil or sirolimus developed 16 severe infectious events requiring hospitalization. No patients died. Overall infections rate was 0.24 person/*100months/risk (95% CI 0.09-0.3). Serious infectious events incidence was higher in patients with ALPS-like compared to others (0.42 versus 0.09; p=0.006) and lower in patients who underwent mycophenolate treatment alone compared to those who started sirolimus after mycophenolate failure (0.04 versus 0.29, p=0.03). Considering only patients who started treatment at the begin of study period, overall cumulative hazard was 18.6% at 60 months (95% CI 3.4-31.4) with higher risk of infectious events after 5 years in ALPS-like patients (26.1% -95% CI 3.2-43.5) compared to other AICs (4% -95% CI 0-11.4; p=0.041).Discussion: To the best of our knowledge, this is the first study describing the infectious risk related to mycophenolate and sirolimus chronic treatment in patients with autoimmune cytopenias and immune dysregulation. Our data highlights that infections rate is very low and mainly related to underlying hematological condition.Conclusions: Mycophenolate and sirolimus represent a safe immunosuppressive therapy in autoimmune cytopenias and immune dysregulation syndromes.